2012
DOI: 10.1016/j.jpainsymman.2011.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parenteral Hydration Therapy Based on the Japanese National Clinical Guideline on Quality of Life, Discomfort, and Symptom Intensity in Patients With Advanced Cancer

Abstract: Guideline-based parenteral hydration therapy contributed to maintaining global QoL and provided satisfaction and a feeling of benefit without increasing discomfort and worsening symptoms and fluid retention signs in patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 21 publications
1
33
1
Order By: Relevance
“…Previous studies have found a tendency of higher prevalence with more hydration 13 15. Our results are in accordance with those; the prevalence was higher in the PF groups for all time frames, although significant only when comparing PF administration the last week with symptom for the last 24 h (table 3).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have found a tendency of higher prevalence with more hydration 13 15. Our results are in accordance with those; the prevalence was higher in the PF groups for all time frames, although significant only when comparing PF administration the last week with symptom for the last 24 h (table 3).…”
Section: Discussionsupporting
confidence: 92%
“…In that study, no statistically significant difference in respiratory distress was found between patients receiving small (<1 L) and large (>1 L) daily volumes of fluid in the last weeks of life 13. Our results are not consistent with theirs, but the differences are also probably due to different research methods (eg, their study group did not have a matched control group) 13.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…4,6,15 One recent study found no relationship between parenteral fluids and development of death rattle, 5 although guidelines still recommend reducing fluids. 16 Pharmacological interventions are routinely used: palliative care texts invariably advocate the off-label use of anticholinergic medications for the treatment of death rattle. 17,18 Research on these pharmacological interventions is more robust but still fails to provide compelling evidence for effective treatment that changes the natural history of the clinical presentation.…”
Section: Significancementioning
confidence: 99%
“…Increased fluid and metabolic loading causes discomfort, edema, and shortness of breath in these patients. [10][11][12] In end-of-life care, providing small amounts fluids or withholding total parenteral nutrition (TPN) to patients with terminal cancer is considered to be acceptable because of alleviation of symptoms or lack of evidence for benefits. 11,13 Nevertheless, withholding or withdrawing ANH conflicts with the idea that providing ANH is part of basic patient care.…”
mentioning
confidence: 99%